FFAR4/GPR120 SEBAGAI TARGET DESAIN DAN PENGEMBANGAN OBAT DIABETES MELITUS TIPE 2 IN SILICO: SUATU TINJAUAN DAN PERSPEKTIF - SAUDALE, FREDY Z.; TOKAN, MERVINA B.; LEO, STEVEN Y.; ATI, SERLY P. (Universitas Nusa Cendana, 2020)
FFAR4/GPR120 is an attractive membrane protein for diabetic drug design. Crystal structure of GPCR membrane proteins is difficult to obtain. Most of GPCR proteins lack experimental 3D structures. Therefore, computational method (in silico) using comparative homology modelling has been widely applied to solve it. To develop FFAR4/GPR120 selective compounds with high specificity, homology modelling of FFAR4/GPR120 can be constructed by utilizing other known GPCR crystal structures. This review article surveys the recent developments in the application of computational approaches in searching for selective agonist ligands and provides a perspective on computational approaches to the development of new drugs targeting FFAR4/GPR120.